Continuity and discontinuity in narratives about ecological change: Understanding artisanal fishers' responses to Climate Change governance - Mouro, C.; Santos, T.; Castro, P. (International Conference on Environmental Psychology, 2017)
In a period of intense debate about the effects of climate change, it is crucial to better understand the psychosocial dimensions involved in how coastal communities respond to the tools that govern the protection of marine resources and to the ideas and values these incorporate. It is especially important to understand the responses of certain groups particularly affected by the changes this governance imposes. In the present study, we will examine how artisanal fishers, confronted with new conservation laws and their assumptions regarding fish scarcity, present their past, present and future. Some authors have suggested that past-present discontinuity is identity-threatening and negative (Breakwell, 1986). Yet, other approaches show how continuities and discontinuities can both be useful in the positive (re-)construction of identities (Greenwood, 2015). We thus examine whether and how accounts of continuity and discontinuity with the past are (1) presented as negative or positive experiences; (2) mobilized to legitimize or delegitimize the ideas and values incorporated in the laws upholding changes to their trade. For this we performed interviews (n=39) to fishers and seafood collectors living in a coastal protected area in the southwest of Portugal. The analysis had two phases. First, the main themes were identified through a lexicometric analysis with IRAMUTEQ. The second phase of the analysis explores how continuities and discontinuities are mobilized across the specific themes and what functions they fulfill in the narratives. Two main clusters emerged from the lexicometric analysis, each divided in two subthemes: A. Fishing and local knowledge, which included A.1 Fishing Tools and Resources, discussing old and new forms of fishing as well as the current situation of fish and seafood, and A.2 Fishing Places and Actions, offering detailed knowledge of fishing places and conditions; and B. Social Relations, divided into B.1 Informal relations, mainly discussing social memory of private sphere relations, and B.2 New institutions and formal relations, debating their relationship with the governance institutions and conservation laws, as well their new forms of local association. The second phase of the analysis showed that threats to continuity linked to decrease in resources are dealt with a strategy that oscillates between acknowledgment and denial of the situation, only sometimes associated to excessive fishing. Discontinuity induced by new tools is generally presented as positive, although it is stressed how such innovations also facilitate excessive fishing. Threats to continuity linked to ecological governance and laws are dealt with by both criticizing and defending some of the aspects of the laws. Overall, the presentation of continuities and discontinuities indicates an ambivalent sense making of current fishing practices and enables resistance to the new laws; yet, discontinuity is not always presented as disruptive: it accommodates desired changes (in tools and fishing conditions) and sometimes opens space for the negotiation and integration of new meanings and actions.